Modeling of soil erosion by water in the provinces of Sikasso and Koulikoro (Republic of Mali) - Bourema , Diarra (Антропогенная трансформация природной среды, 2021)
Soil along water is arguably the most precious resource on the planet. In addition to its economic benefits, soil provides critical biological services [7]. Despite its pillar functions for society, soil is often overlooked and thus is subjected to degradation and erosion. Soil erosion represents a serious global threat to land, freshwater, and oceans [3]. In Western Africa, erosion is perceived as a critical threat to the livelihoods of millions of people. This study attempts to assess and map the potential annual soil loss in the provinces of Sikasso and Koulikoro (republic of Mali). Spatial modeling of soil loss by rainfall for the year 2018 was provided using rainfall data derived from the European Joint Research Center, the Soil Map of the World (FAO), digital elevation model (SRTM), vegetation activity (MODIS / Terra). Methods of calculation were based on the Remote Sensing and the Revised Universal Soil Loss Equation (RUSLE). The Geoinformation processing of the RUSLE subcomponents involved the use of the LS-factor algorithm of the System for Automated Geoscientific Analyses (SAGA) and the Raster calculator of the ArcGIS tool box. The potential soil loss within the area ranged from 0.02 ton/ha/year to 98.87 tons/ha/year with a mean of 1.63 ton/ha/year. The spatial pattern of the erosion showed a rate of 0.02 to 1 ton/ha/year for 39% of the territory, 1 to 3 tons/ha/year for 47.58%, while 0.01% experienced a rate of more than 50 tons/ha/year. This study despite its match with the result of the global soil loss by water established by Borreli et al (2020) [3], needs to be verified by direct measurements.